1983
DOI: 10.1111/j.1476-5381.1983.tb10520.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modification of sympathetic activity on responses to ligation of a coronary artery in the conscious rat

Abstract: Ligation of a coronary artery was performed in conscious rats whose sympathetic system activity had been altered by various treatments. β‐Adrenoceptor blockade with acute (0.2 mg kg−1 plus 0.1 μg kg−1 min−1) or chronic (50–60 mg kg−1 daily for 12 days) propranolol treatment had little effect on arrhythmias, or other responses to ligation. Abrupt withdrawal of chronic propranolol two days before ligation was also without effect. Reduction of sympathetic activity acutely with labetalol (5 mg kg−1), or chronicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 7 publications
(7 reference statements)
1
20
0
Order By: Relevance
“…In addition, the reported antiarrhythmic actions of a-adrenoceptor antagonists in rat isolated ischaemic hearts was not attributed to xadrenoceptor antagonism (Daugherty & Woodward, 1982), rather to 'membrane stabilizing' effects of the drugs studies (Bralet et al, 1985). Finally, we have shown that in rats, neither combined a-and P-adrenoceptor blockade nor sympathectomy reduced arrhythmias (Botting et al, 1983), while graded ablations in the CNS and catecholamine infusions did not influence arrhythmias in a manner consistent with a role for a-(or P-)adrenoceptors in arrhythmogenesis during acute myocardial ischaemia (Curtis et al, 1985c). Therefore we consider it highly improbable that verapamil reduced ischaemia-induced arrhythmias in conscious rats via myocardial a-adrenoceptor antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reported antiarrhythmic actions of a-adrenoceptor antagonists in rat isolated ischaemic hearts was not attributed to xadrenoceptor antagonism (Daugherty & Woodward, 1982), rather to 'membrane stabilizing' effects of the drugs studies (Bralet et al, 1985). Finally, we have shown that in rats, neither combined a-and P-adrenoceptor blockade nor sympathectomy reduced arrhythmias (Botting et al, 1983), while graded ablations in the CNS and catecholamine infusions did not influence arrhythmias in a manner consistent with a role for a-(or P-)adrenoceptors in arrhythmogenesis during acute myocardial ischaemia (Curtis et al, 1985c). Therefore we consider it highly improbable that verapamil reduced ischaemia-induced arrhythmias in conscious rats via myocardial a-adrenoceptor antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…In all rats, irrespective of the time of death, the occluded zone was measured by dye exclusion ex vivo, whereas infarct zones were determined only for rats surviving 24 h. The techniques used for these determinations, and the statistical methods employed for analysis of all the variables measured have been described in full elsewhere (Botting et al, 1983;Johnston et al, 1983;Curtis et at., 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of covariance in over 250 conscious rats showed no correlation between arrhythmias and blood pressure and/or heart rate . We have also shown that, in conscious rats, propranolol (acute or chronic treatment), labetalol, or 6-hydroxydopamine (6-OHDA) plus adrenalectomy do not influence arrhythmias produced by coronary occlusion (Botting et al, 1983). However, others, using conscious rats, have found chronic treatment with P-adrenoceptor blockers reduces arrhythmias (Siegmund et al, 1979;Szekeres, 1979).…”
Section: Introductionmentioning
confidence: 95%